2003
DOI: 10.1159/000070108
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Color Duplex Sonography in Cerebrovascular Disease: A Systematic Review

Abstract: Transcranial color-coded duplex sonography (TCCS) enables the reliable assessment of intracranial stenoses (sensitivity 94–100%, specificity 99–100%), occlusions (middle cerebral artery: sensitivity 93–100%, specificity 98–100%) and cross-flow through the anterior (sensitivity 98%, specificity 100%) and posterior (sensitivity 84%, specificity 94%) communicating arteries without using potentially dangerous compression tests, as well as the midline shift in hemispheric infarcts. Ultrasound contrast agents (UCAs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 95 publications
(152 reference statements)
0
36
0
4
Order By: Relevance
“…Unlike cases of extracranial ICA disease, stenosis gradation of the intracranial ICA has not been calculated. 17,18 With MRA, intracranial ICA stenosis in the C5 as well as the C3 and C1 segments is frequently indicated by flow-void artifacts, especially when using time-of-flight sequences, because of the inherent signal-intensity loss of parallel imaging, which can only be compensated in part by the use of MR imaging contrast agents. 19 Due to these MRA artifacts, calculation of ICA stenosis gradation is difficult, and semiquantitative scales, rather than percentages of stenosis, are frequently used to describe the lesion.…”
mentioning
confidence: 99%
“…Unlike cases of extracranial ICA disease, stenosis gradation of the intracranial ICA has not been calculated. 17,18 With MRA, intracranial ICA stenosis in the C5 as well as the C3 and C1 segments is frequently indicated by flow-void artifacts, especially when using time-of-flight sequences, because of the inherent signal-intensity loss of parallel imaging, which can only be compensated in part by the use of MR imaging contrast agents. 19 Due to these MRA artifacts, calculation of ICA stenosis gradation is difficult, and semiquantitative scales, rather than percentages of stenosis, are frequently used to describe the lesion.…”
mentioning
confidence: 99%
“…1 Postoperative carotid thrombosis is preceded by increasing embolization, which can be detected by transcranial Doppler, and there is increasingly convincing evidence that the postoperative transcranial Doppler signals represent platelet microemboli. 2 We have previously shown that the rate of postoperative embolization is related to the inherent responsiveness of the patients' platelets to adenosine diphosphate (ADP). 3 Those patients who developed high numbers of emboli in the first 1 to 2 hours postoperatively, and were therefore, by definition, at higher risk from stroke, 4 -7 had platelets that showed a strong aggregatory response to ADP preoperatively despite the use of a standard 150-mg dose of aspirin in all the patients.…”
mentioning
confidence: 99%
“…Transcranial Doppler ultrasound (TCD) is an accurate and widely used complementary examination for neurovascular study 20,21 . It has been validated for monitoring endovascular carotid balloon occlusion tests for almost 20 years 22 with good results 2,17,19 .…”
Section: Discussionmentioning
confidence: 99%